2020
DOI: 10.1038/s41598-020-61000-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of tomato protein kinases embedding guanylate cyclase catalytic center motif

Abstract: Guanylate cyclases (GCs) are enzymes that catalyze the reaction to produce cyclic GMP (cGMP), a key signaling molecule in eukaryotes. Nevertheless, systemic identification and functional analysis of GCs in crop plant species have not yet been conducted. In this study, we systematically identified GC genes in the economically important crop tomato (Solanum lycopersicum L.) and analyzed function of two putative tomato GC genes in disease resistance. Ninety-nine candidate GCs containing GC catalytic center (GC-CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…The available data in the literature indicate that cGMP and enzymes with in vitro confirmed GC activity are involved in the response to pathogen infection [ 4 , 5 , 6 , 7 , 27 , 28 ]. Active resistance is triggered by pathogens and involves biochemical and molecular responses.…”
Section: Resultsmentioning
confidence: 99%
“…The available data in the literature indicate that cGMP and enzymes with in vitro confirmed GC activity are involved in the response to pathogen infection [ 4 , 5 , 6 , 7 , 27 , 28 ]. Active resistance is triggered by pathogens and involves biochemical and molecular responses.…”
Section: Resultsmentioning
confidence: 99%
“…Several of the LRR RLK candidate guanylate cyclases (moonlighting kinases) identified in Arabidopsis [ 37 ] have since been shown to contain both kinase and guanylate cyclase activity at least in vitro. These include the brassinosteroid receptor, brassinosteroid insensitive 1 (AtBRI1; AT4G39400) [ 37 , 80 ], phytosulfokine receptor 1 (AtPSKR1; AT2G02220) [ 81 , 82 , 83 ], the DAMP receptor for Arabidopsis plant elicitor peptide 1 (AtPEP1), AtPEPR1 (AT1G73080), and its tomato homologs SlGC17 and SlGC18 [ 84 , 85 ]. BRI1 and PSKR1 are both important in plant growth, while PEPR1 is involved in plant immunity.…”
Section: Moonlighting Kinasesmentioning
confidence: 99%
“…Both PEPR1/2 carry a guanylate cyclase catalytic center with conserved residues crucial for catalysis embedded in its kinase domain [ 84 , 120 ], but so far only the enzymatic activity of PEPR1 has been experimentally demonstrated [ 84 ]. Recombinant protein studies have demonstrated that AtPEPR1, H. hybridum HhPEPR1, and tomato homologs SlGC17 and SlGC18, can all generate cGMP [ 84 , 85 , 136 ]. Downstream signaling following PEP activation involves characteristic pattern induced responses including increased gene transcription that is enhanced in the presence of calcium possibly entering cells by cyclic nucleotide gated channels (CNGC) [ 84 , 125 ].…”
Section: Moonlighting Kinasesmentioning
confidence: 99%
“…x(3) [VIL] x (4) [KR] is present in the catalytic center of guanylyl cyclases of several A. thaliana proteins, including brassinosteroid receptor AtBRI1 [8], wall-associated kinase like 10 AtWAKL10 [20], Pep1 receptor AtPepR1 [12], phytosulfokine receptor AtPSKR1 [9], nitric oxide-binding GC AtNOGC1 [21], plant natriuretic peptide receptor AtPNP-R1 [22], H. hybridum HpPepR1 [13], and 99 GC candidates in Solanum lycopersicum [15]. As presented in Figure 1B, the red amino acids at positions 1, 3 and 14 within the search motif are functionally assigned residues [16].…”
Section: The Mentioned Motif [Rks] [Yfw] [Gcth] [Vil] [Fv]mentioning
confidence: 99%